Insurance as the Most Attractive Method to Prevent Risk in Micro-Enterprises - Soroka-Potrzebna, Hanna (Studia Oeconomica Posnaniensia, 2026)
Ways to prevent risk in enterprises are numerous but not all of them are suitable for the special group that are micro-enterprises. Analysis of the most common methods permits an indication of the most attractive alternative, which is risk transfer, and specifically the insurance of business activities.